The microfoundations of organizational ambidexterity: A systematic review of individual ambidexterity through a multilevel framework - Eva M. Pertusa-Ortega; José Francisco Molina Azorín; Juan José Tarí; Jorge Pereira-Moliner; María D. López-Gamero (BRQ Business Research Quarterly, 2021)
The analysis of ambidexterity at the individual level may help to open the black box of organizational ambidexterity and to address the microfoundations of the exploration/exploitation dilemma in order to know how it can be achieved. The purpose of this article is to examine the main characteristics, antecedents, and consequences of individual ambidexterity, highlighting several key theoretical and methodological issues. Through a systematic literature review, we synthesize and integrate knowledge about individual ambidexterity, identifying opportunities and challenges for future research. We propose a multilevel framework that includes antecedents, consequences, and contingent effects of individual ambidexterity and their relationships. This multilevel framework may help to overcome the micro-macro divide in the management field. We also provide a synthesis of future research proposals.
Keywords: M10; E41; E43; E51; M12; M52; 650; Microfoundations; individual ambidexterity; systematic review; multilevel research